TIPE VERBA BAHASA PERANCIS DAN PERWUJUDANNYA PADA KLAUSA - Roswita Lumban Tobing (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe types of verbs and their realizations in clauses in French. The data were collected from books on the French language system. The data were analyzed using a structural approach combined with referential semantics to check the acceptability of verb uses in clauses. The results are as follows. First, an intransitive verb in a clause serves as a predicate that describes the subject action without an object. Second, a transitive verb must be followed by a direct or an indirect object which can be placed in front of the verb. Third, a dual-type verb can be a transitive verb or an intransitive verb. Fourth, in the passive voice, the construction of the main verb is ‘participe passé’ that must be accompanied by the auxiliary verb ‘etre’.